PENINGKATAN KEMAMPUAN SISWA KELAS VII MTS ALKHAIRAAT BULURI MENULIS SURAT PRIBADI MELALUI METODE PENUGASAN - Fitriyanti Hasanah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
The formulation of the problem of this research is whether the ability of students to write personal letters can be improved. This study aims to improve the ability of class VII A students of MTs Alkhairaat Buluri to write personal letters through assignment methods. And this research can be useful for students, for teachers, and for schools. The design of this study was classroom action research (PTK) which was carried out for two cycles, which included planning, implementation, observation, and reflection. The technique of collecting data is through evaluating the performance of writing personal letters and observing students and teachers. The results of this study proved to be significant (1) the assignment method proved to be able to effectively improve the ability to write personal letters of class VII A MTs Alkhairaat Buluri students. The increase in learning outcomes is indicated by the average grade of 64 with the percentage of classical learning reaching 55% (less) or just 10 students completing from 18 students who participated in the evaluation in the first cycle (according to the school KKM) and (2) learning outcomes indicated by the average value of 85 with the percentage of classical learning reached 88% in the second cycle with good qualifications or 16 students completed from 18 students who participated in the evaluation, so the research hypothesis was accepted